Kualitas Pelayanan Publik di Puskesmas Anggrek Kabupaten Gorontalo Utara - Nur Yusri Adam; Sri Yulianty Mozin; Alifiyah Agussalim (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the Quality of Public Services at the Anggrek Health Center, North Gorontalo Regency. This study was conducted based on three aspects that influence the quality of public services, namely: (a) official work motivation (b) community supervision and (c) implementation of spatial planning policies. This study uses a qualitative descriptive method with data collected through observation, interviews, and documentation. Data analysis was carried out through three stages: Data Reduction, Data Presentation, and Conclusion Drawing. The results of the study indicate that the Quality of Public Services at the Anggrek Health Center, North Gorontalo Regency, as seen from the three aspects that influence the quality of public services, is significantly influenced by employee work motivation which is still uneven so that services at the Anggrek Health Center have not been realized properly. Community supervision has been carried out through various mechanisms, such as suggestion boxes, satisfaction surveys, reports through NGOs and village officials, to external assessments from institutions such as the Ombudsman, which have become effective means to encourage accountability, transparency, and professionalism of service officials. The implementation of spatial planning policies on the quality of public services at the Anggrek Health Center has succeeded in creating a more structured, focused, and responsive service system to patient needs. This policy not only supports the effectiveness of health workers' work through the separation of space according to service clusters, but also increases public satisfaction by providing a clearer and easier-to-understand service flow.